The Concept of Child and Parent Relationships from the Perspective of Qur'anic Parenting in Tafsir Al Munir - Karim, Bustanul; Raya, Ahmad Thib; Kholilurrahman, Kholilurrahman (Bulletin of Early Childhood, 2023)
The parenting relationship between children and parents has recently attracted a lot of attention. Issues of neglect and violence are often children who become victims. This has become a highlight not only among educational practitioners, but also among theologians (religious scholars), including commentators on the interpretation of the Al-Qur'an. This research aims to provide an in-depth understanding of the parenting relationship between children and parents by exploring the meaning of the term child in the Al Qur'an, as well as identifying the implications of its meaning in the context of parenting relationships. The method used in this research is maq?shid? thematic with the main object of study being the interpretation of al-Mun?r by Wahbah Zuhaili. The findings show differences in the substance of the meaning of each child term in the Al-Qur'an, reflecting the dimensions of the relationship between children and parents which involve aspects of biological, psychological, sociological and physical development. The emphasis on the relationship between children and parents is reflected through messages about attachment, rights and obligations, as well as reciprocal dynamics that begin when the child is in the womb until he grows into an independent person. Keywords: Relationships, Quranic Parenting, Tafsir al Mun?r